Comparison of wormlion behavior under man-made and natural shelters: urban wormlions more strongly prefer shaded, fine-sand microhabitats, construct larger pits and respond faster to prey. Issue 1 (1st March 2019) - Samocha, Yehonatan; Scharf, Inon
Abstract: Urban habitats differ from their natural surroundings in various aspects, such as a higher temperature and a distinct species composition. It is therefore not surprising that animal behavior too differs between these habitat types. We studied the foraging and habitat selection behavior of a pit-building predator, a wormlion, originating from either an urban or a more natural site. Wormlions occur in nature under structures that provide shelter from sunlight and rain, such as caves, and are also common in cities, occurring under artificial shelters. Wormlions construct pit-traps to hunt arthropods, and the pits constructed by urban wormlions were larger than those constructed by wormlions from caves. Urban wormlions responded faster to prey falling into their pit, probably leading to a higher capture success. We suggest that these 2 findings indicate the higher investment of urban wormlions in foraging, resulting from the higher abundance of potential prey in the city. Urban wormlions were choosier regarding their preferred microhabitat. While both fine sand and shaded microhabitats were preferred by wormlions, urban wormlions demonstrated a greater preference for such conditions. We suggest that relocation is more likely to lead wormlions in cities to find microhabitats of a higher quality compared with wormlions inhabiting caves. This is probably due to the larger areas in the city available for wormlions. Wormlions from the caves possessed more lipids, suggesting that they employ a conservative growth strategy, intended to contend with the uncertainty of prey arrival, in contrast to the city, where potential prey are more abundant.